Analysis on EMF characteristics for torque ripple reduction in BLAC motor intended for HVLS fan application - Nurfaezah Abdullah; Raja Nor Firdaus Raja Othman; Kasrul Abdul Karim; Lim Seng Tat (Institute of Advanced Engineering and Science, 2020)
This paper analyzes the harmonic characteristics of electromagnetic force (EMF) in Brushless Alternating Current (BLAC) motor for High Volume Low Speed (HVLS) fan application. Vibration and noise are one of the main crucial things in HVLS fan application. It comes from torque ripples which can be detected by harmonics of Electro Magnetic Force (EMF). Commonly, there are a few methods to eliminate the noise and vibrations issue, but most literatures only focus on small motor and not intended for HVLS fan application. Thus, the objective of this paper is to eliminate the harmonics content in EMF at early stage design. Through EMF harmonics the expected torque produced could be used to select proper slot-pole number in order to eliminate the noise and vibrations issue. In here, the analysis involves three different slot-pole numbers which are 18s/20p, 12s/10p and 9s/8p BLAC model, respectively. All models have similar volume of permanent magnet. The analysis is carried out using FLUX 2D Finite Element Analysis (FEA) for EMF computational and transient torque computation. Later, Fast Fourier Transform (FFT) analysis is used to calculate the harmonics of EMF. The analysis stage includes the EMF parameter analysis, harmonics and torque ripples analysis. It was found that 18s/20p has higher output torque with the lowest 5% torque ripple value. As a conclusion, this paper presents low torque ripple in point of view of the EMF characteristics in designing HVLS fan.